The Role of Family, Friend, and Significant Other Support in Well-Being Among Transgender and Non-Binary Youth. Issue 4 (8th August 2019) - Weinhardt, Lance S.; Xie, Hui; Wesp, Linda M.; Murray, Jennifer R.; Apchemengich, Immaculate; Kioko, David; Weinhardt, Caleb B.; Cook-Daniels, Loree
Abstract: Transgender youth have been found to experience mental health disparities, experiencing greater rates of depression and anxiety than their cisgender counterparts. This mixed-methods study examined social support and how it is related to well-being and resilience among transgender youth. A sample of 154 transgender and gender nonbinary youth (13 to 21 years) completed a survey at a Pride event in a Midwest US city. The survey assessed living as one's affirmed gender, social support, finding meaning in life, quality of life, mental health, and resilience. A focus group ( n = 8) discussed their experiences of support. Ninety-two percent reported being assigned female at birth; 27% identified as transmasculine, 38% genderqueer, and 24% more than one gender. Family support was positively associated with the likelihood of living as one's affirmed gender. Support from friends and significant others were not significant indicators of living as one's affirmed gender. Participants with greater family support were less likely to report that they had a mental health problem in the past year. Friend support was positively associated with connectedness and finding meaning in life. Qualitative analyses identified how transgender youth define and experience support in their lives. Future studies should examine the use of family counseling and building communication skills for transgender youth health and resilience interventions.